Corporate Culture - Maulidi, Fiqi; Hasan, Sifa Alviana; Anshori, Mochammad Isa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Organizational culture has an important role in shaping patterns of behavior within the company. Organizations need to pay attention to the ongoing culture and carry out developments so that they can control the culture to continue to run positively and profitably for the organization. The purpose of writing this article is to examine the literature on corporate culture. The writing uses the literature review study method or literature review related to organizational culture to then be read and studied so as to provide an overview and literature about organizational culture.